Study of Efficiency of Photochemical Oxidation Process with UV/Peroxidisulfate for Removal of Alizarin Red S from Aqueous Solutions - Fariba Hafezi; Mohammada Amin Karami; Bahram kamarehie; Ali Jafari; Mansor Ghaderpoori; Mohammad Bazdar; Ellahe Razipour (Mazandaran University of Medical Sciences, 2016)
Introduction and purpose: Treatment of dye wastewater produced by textile industries is a major challenge for the environment. About 15% of the total produced dyes in the world are released in sewages during dyeing activities. Alizarin red S (ARS), a synthetic dye produced from Alizarin sulfonate is the most widely used dye in the textile industry. The aim of this study was to remove ARS dye from aqueous solutions through advanced photochemical oxidation process using UV/peroxidedisulfate. Methods: In this study, the effect of pH, concentration of persulfate, dye concentration, and UV radiation on removal of ARS were studied in laboratory scale using a reactor containing UV-C lamp (6 watts) by batch method. ARS concentration was determined by UV/Visible spectrophotometer. Results: The results showed that removal efficiency increased by increasing the disulfate concentration, ultraviolet radiation intensity, and reaction time and decreased by increasing dye concentration and pH. The optimum condition was obtained at pH=7, peroxidisulfate concentration of 0.02 Mmol/L, and 50 mg/L dye concentration. Also, the ARS removal by UV/peroxidisulfate process follows a first-order kinetic. Conclusion: Due to the high removal efficiency of this process in removing ARS (96.5%), use of this process can be a good choice in the treatment of dye and industrial wastewater.